Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1984
DOI: 10.1115/84-gt-276
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Chemical Reactivity and Dimensional Growth in Machining of Titanium Alloys

Abstract: Machining of aero-gas turbine components made of titanium alloys, using different combination of tools, cutting fluids and machining parameters revealed two important characteristics namely, chemical reactivity and dimensional growth. The former is pronounced when machined with carbide tools using Sulphur based cutting oils. The reactivity was not noticeable when machined either with CBN or ceremet tools, contrary to the reports in the literature. This mechanism of chemical reaction has been studied including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In fact, as Moreno et al (2005) have shown, titanium reacts with carbon at elevated temperatures. However, Subhas and Katti (1990) claims that titanium is highly reactive both with the materials of the tools and with the cutting fluids. To ensure that carbon does appear due to diffusion from the tool, various machining tests were realized under dry cutting conditions.…”
Section: Sem Observationmentioning
confidence: 99%
“…In fact, as Moreno et al (2005) have shown, titanium reacts with carbon at elevated temperatures. However, Subhas and Katti (1990) claims that titanium is highly reactive both with the materials of the tools and with the cutting fluids. To ensure that carbon does appear due to diffusion from the tool, various machining tests were realized under dry cutting conditions.…”
Section: Sem Observationmentioning
confidence: 99%
“…Furthermore, titanium is known to be chemically reactive with atmospheric gases such as oxygen at high temperatures, as well as with some elements like carbon. Upon reaction with carbon, titanium forms hard compounds on the alloy surfaces [15], resulting in the wear of the tool rake. This process is initiated by the diffusion of carbon from the tool to the work material and is followed by a reaction with Ti atoms to form a TiC layer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Few more researchers [6][7] have also reported the dimensional instability effect due to residual stress during the machining on conventional steel but not on Inconel 718 superalloys. Subhas, et al (8] reported dimensional instability phenomenon on titanium alloys but not on Inconel 718. The studies conducted by Subhas [12] on other nickel based superalloys like Nimonic-90, Inconel 901 reveals that there is no appreciable dimensional instability phenomenon, on these alloys.…”
Section: Introductionmentioning
confidence: 98%